Characteristics of Bovine and Ovine Whey Protein Concentrates Obtained by Ultrafiltration and Diafiltration Using Different Configuration Processes - Fernandes Henriques, Marta Helena; Pereira, Carlos José Dias; Mendes Gil, Maria Helena (Challenges and Advances in Chemical Science Vol. 1, 2021)
The goal of this study was to valorize bovine and ovine cheese whey from small and medium cheese manufacturing plants by producing liquid and dry whey protein concentrates (LWPC and WPC). The flexibility provided by batch ultrafiltration (UF) and diafiltration (DF) enabled the production of liquid bovine WPC with protein contents ranging from 43 to 66% (dry basis) and ovine WPC with protein contents ranging from 61 to 87% (dry basis). Diafiltration, performed in sequential dilution mode (DFsdm) did not significantly improve the composition of WPC liquid products comparing to the results achieved by conventional UF. In comparison to traditional UF, using DF in volume reduction mode (DFvrm) enhanced protein content by more than 20%. Ovine products have greater protein content (62-84% on a dry basis), which makes them more appealing for manufacturing. Protein profiles varied with the whey origin and with the concentration process. By using batch DFvrm it was possible to obtain richer protein products free of low molecular weight compounds in comparison to the DFsdm mode. Finally, it can be concluded that use of membrane technology allows the recovery and direct valorization of the whey components in medium and small cheese companies, solving their environmental problems and contributing to the circular economy.